Cross-reactivity of hepatitis C virus specific vaccine-induced T cells at immunodominant epitopes. - Kelly, C; Swadling, L; Brown, A; Capone, S; Folgori, A; Salio, M; Klenerman, P; Barnes, E (Wiley, 2015)
Viral diversity is a challenge to the development of a hepatitis C virus (HCV) vaccine. Following vaccination of humans with adenoviral vectors, we determined the capacity of T cells to target common viral variants at immundominant epitopes ex vivo. We identified two major variants for epitopes NS3(1073) and NS3(1446), and multiple variants for epitope NS3(1406) that occurred in >5% of genotype 1 and 3 sequences at a population level. Cross-reactivity of vaccine-induced T cells was determined using variant peptides in IFN-γ ELISPOT assays. Vaccine-induced T cells targeted approximately 90% of NS3(1073) genotype 1 sequences and 50% of NS3(1446) genotype 1 and 3 sequences. For NS3(1406), 62% of subtype-1b sequences were targeted. Next, we assessed whether an in vitro priming system, using dendritic cells and T cells from healthy donors, could identify a variant of NS3(1406) that was maximally cross-reactive. In vitro priming assays showed that of those tested the NS3(1406) vaccine variant was the most immunogenic. T cells primed with genotype 1 variants from subtype 1a or 1b were broadly cross-reactive with other variants from the same subtype. We conclude that immunization with candidate HCV adenoviral vaccines generates cross-reactive T cells at immunodominant epitopes. The degree of cross-reactivity varies between epitopes and may be HCV-subtype specific.